High fracture risk after long term oral bisphosphonates and vitamin D - Ringe, J. D.; Schacht, E. (Osteologie, 2013)
Introduction: Optimal duration of bisphosphonate (BP) therapy has not been defined. A recent FDA publication suggests periodically re-evaluating patients on BP. Those with low risk may discontinue BP after 3–5 years, those still at high risk may benefit from ongoing BP.Patients and methods: We compared continued BP therapy plus plain vitamin D to BP plus alfacalcidol in patients still at a significantly increased fracture risk after an average of 4.3 years of BP plus plain vitamin D use over two more years. The study was based on retrospective chart analysis and followed 214 patients (167 female, 47 male). Among these 145 continued alendronate (ALN) and 69 risedronate (RIS). In addition, group A (n = 106) received 800 IU/d plain vitamin D plus 1200 mg/d calcium as before, while patients in group B (n = 108) were switched from plain vitamin D to 1 μg/d alfacalcidol plus 500 mg/d calcium. The respective proportions of males and females and patients with ALN or RIS intake did not differ between group A and B. BMD was measured at 0, 12 and 24 months at lumbar spine (LS) and femoral neck (FN) by DXA. Lateral spine morphometry assessed prevalent and incident vertebral fractures. Recorded were the number of falls and fallers 2 years before and during the trial, back pain (VAS 0–10), adverse events (AE) and prevalent and incident non-vertebral fractures. We also conducted subgroup analyses in four groups – female, male, ALN, RIS on all endpoints.Results: BMD at LS did not change significantly over two years with +1.1 % in group A, but increased significantly with BP plus alfa-calcidol by + 5.5 % (B vs. A p < 0.01). At the FN site the respective changes were +0.6 % and +3.4 % (p < 0.01). The average number of falls per patient-year was reduced by 12 % in A (ns) and by 44 % in B (p < 0.03). There was a significant decrease in average back pain score with BP plus alfa calcidol vs. BP plus plain vitamin D after two years (p < 0.02). The number of patients with new vertebral fractures did not significantly differ between A and B. There were however significantly less non-vertebral fractures with alfacalcidol (p < 0.05). The above was found significant in all subgroups for nearly all endpoints. The number of adverse events (AE) did not differ between groups. No serious AE were observed.Discussion: The data show that in male and female osteoporosis patients still at risk after 4.3 years on oral BP a continuation of BP plus alfacalcidol is superior to ongoing therapy with BP plus plain vitamin D.
Keywords: Osteoporosis; long-term bisphosphonate; treatment continuation; vitamin D; alfacalcidol